VALIDATION OF DIVERSE INFORMATION TO PREPARE AN INTERACTIVE BOOKLET FOR FAMILIES OF AUTISTIC CHILDREN - Weissheimer-Kaufmann, Gisele; Mazza, Verônica de Azevedo; Ruthes, Victoria Beatriz Trevisan Nobrega Martins; Oliveira, Lucas Ferrari de (Cogitare Enfermagem, 2022)
Objective: to validate content and face of diverse information to prepare an interactive booklet for families of children with Autism Spectrum Disorder. Method: a methodological research study conducted in Curitiba-PR, Brazil, with 86 experts between June and November 2020 and using the Delphi technique. An instrument with variables about relevance of the content, clarity and objectivity and scientific topicality was used for data collection. In data analysis, the Content Validity Index was set at ≥75%. Results: the content about the characteristics of autistic children, their diagnosis, behavior and rights was considered valid by the experts in the first round. The diverse information about the signs in autistic children and their future were validated in the second round, after the reformulations suggested by the experts. Conclusion: this educational resource has the potential to contribute in health education for the families of autistic children.